Prediction of the endocrine-disrupting ability of 49 per- and polyfluoroalkyl substances: In silico and epidemiological evidence. (March 2022) - Yu, Shuling; Ren, Jing; Lv, Zhenxia; Li, Rui; Zhong, Yuyan; Yao, Wu; Yuan, Jintao
Abstract: The toxic effects of per- and polyfluoroalkyl substances (PFASs) on humans are mediated by nuclear hormone receptors (NHRs). However, data on the interaction of PFASs and NHRs is limited. Endocrine Disruptome, an inverse docking tool, was used in this study to simulate the docking of 49 common PFASs with 14 different types of human NHRs. According to the findings, 25 PFASs have a high or moderately high probability of binding to more than five NHRs, with androgen receptor (AR) and mineralocorticoid receptor (MR) being the most likely target NHRs. Molecular docking analyses revealed that the binding modes of PFASs with the two NHRs were similar to those of their corresponding co-crystallized ligands. PFASs, in particular, may disrupt the endocrine system by binding to MR. This finding is consistent with epidemiological research that has linked PFASs to MR-related diseases. Our findings may contribute to a better understanding of the health risks posed by PFASs. Graphical abstract: Image 1 Highlights: Typical PFASs were screened for evaluating their endocrine disrupting potential. 25 PFASs have high or sub-high binding probability with more than 5 nuclear receptors. Prediction accuracy was validated by re-docking, literatures and epidemiological data. The modes of PFASs binding to androgen and mineralocorticoid receptor were analyzed. Possible effect of PFASs on MR was first found and validated by epidemiology study.